(3GdJejjR aj JNQjL CMGOjK TQM GdhLjRs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdMi ef GdejJ heNQL GdejJ ef GdMi GdYdje HeG JNai GdUOhQ hJHOjg ef cd TjA s
(3BNQgG (B:s
(3ced gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3cJGH GdhLjR dMLI GdESdGe GdZRGdjs
(3hTQMg GdeSei aJM GdYRjR Ydi cJGH GdhLjR ddQGaYj GdeJhai (B623 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B485s
Keywords: (3GdMOjK h GdeUWdMs